Investigating Teachers’ Roles in Forming EFL Learners’ Self- Confidence: A Lesson Learned for Young Learners - Juliani; Febrina Dafit (Journal of Language and Literature Studies, 2024)
Trust in oneself is a crucial aspect of personality development for students. The role of teachers is pivotal in fostering this self-trust among students. However, the implementation of this role often falls short, leading to instances where students lack confidence, such as feeling embarrassed when answering questions in front of the class. This study aims to delve into the teacher's role in cultivating students' self-trust, particularly among young learners in elementary schools. It employs a descriptive qualitative approach, utilizing observation sheets, interview guidelines, and documentation to gather data. The data is analyzed qualitatively through techniques such as data condensation, data display, and drawing conclusions. The findings reveal several key roles that teachers play in nurturing EFL (English as a Foreign Language) learners' self-confidence, including acting as motivators, providing feedback, facilitating communication, and offering information. Implications for further studies include exploring the effectiveness of specific teaching strategies in enhancing students' trust in themselves and investigating the long-term effects of teacher-student interactions on self-confidence development.